Assessment of Sensory Processing and Executive Functions in Childhood: Development, Reliability, and Validity of the EPYFEI - Romero-Ayuso, Dulce; Jorquera-Cabrera, Sara; Segura-Fragoso, Antonio; Toledano-González, Abel; Rodríguez-Martínez, M. Carmen; Triviño-Juárez, José Matías (Frontiers in Pediatrics, 2018)
The aim of this study was to determine the psychometric properties of the “Assessment of Sensory Processing and Executive Functions in Childhood” (EPYFEI), a questionnaire designed to assess the sensory processing and executive functions of children aged between 3 and 11 years. The EPYFEI was completed by a sample of 1,732 parents of children aged between 3 and 11 years who lived in Spain. An exploratory factor analysis was conducted and showed five main factors: (1) executive attention, working memory, and initiation of actions; (2) general sensory processing; (3) emotional and behavioral self-regulation; (4) supervision, correction of actions, and problem solving; and (5) inhibitory. The reliability of the analysis was high both for the whole questionnaire and for the factors it is composed of. Results provide evidence of the potential usefulness of the EPYFEI in clinical contexts for the early detection of neurodevelopmental disorders, in which there may be a deficit of executive functions and sensory processing.